2010
DOI: 10.4314/bajopas.v2i1.58543
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malarial parasites in pregnant women attending Sir Muhammad Sunusi Specialist Hospital, Kano, Nigeria

Abstract: A total of 300 blood samples of pregnant women were tested to determine the prevalence of malarial parasite using Leishman's stain method. Out of which, 155 (51.7%) were found to be M.P positive, while 145 (48.3%) were M.P negative. 85 (54.8%) of M.P positive had the highest percentage as the primigravidae followed by 70 (45.16%) as multigravidae. Observation have shown that there was a high prevalence of 76 (49.03%) positive patients in the month of August followed by September with 44 (34.19%) as well as 26(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
2
4
2
Order By: Relevance
“…Also lower than that found in Gambia was 56.1% [3]. In Nigeria from 36.5% -51.7% [11,12]. Our finding was greater than that found in pregnant women in India 5.4% [13].…”
Section: Discussioncontrasting
confidence: 60%
“…Also lower than that found in Gambia was 56.1% [3]. In Nigeria from 36.5% -51.7% [11,12]. Our finding was greater than that found in pregnant women in India 5.4% [13].…”
Section: Discussioncontrasting
confidence: 60%
“…The highest rate of infection was among Primigravidae aged 20 -27 years, which accounted for 78.33% of the incidence; this was followed by Secundigravidae aged 28 -35 years, which accounted for 72.62% of the incidence and lastly the group with the least infection in the population was the Multigravidae aged 36 -43 years, which accounted 54.35%. This agrees with the findings ofSuleiman(1998), Taura and Oyeyi, (2009), Raimi andKanu (2010), Ivoke et al, (2013),who said immunity against malaria increases with age and parity as well. Furthermore WHO (2004), revealed that in highly endemic areas infection was uncommon among Multigravidae and more common in Primiand Secundigravidae.…”
Section: Discussionsupporting
confidence: 92%
“…Among the plausible explanations of these result is that pregnant women are more vulnerable to malaria infection (72%). This result (72%) reflects the findings of Taura and Oyeyi (2009) which showed a high prevalence of malaria infection among pregnant women (51.7%) out of 300 pregnant women tested. The high level of the malaria infection from this study could be to the time of the study as rainy season provides abundant sites for the vector proliferation and a suitable temperature required WHO(1994).…”
Section: Discussionsupporting
confidence: 85%
“…This variation can be attributed to different climatic conditions, less rainfall, and surface water that serve as mosquito breeding sites. Previous studies from Kano State showed that 62.5 % (250/400) of the patients attending two hospitals in Kano Metropolis and 51.7 % (155/300) of the pregnant women attending antenatal clinic at a specialist hospital were malaria-positive [ 33 , 34 ]. A similar high prevalence (61.3 %) was reported recently among pregnant women attending Aminu Kano Teaching Hospital [ 35 ].…”
Section: Discussionmentioning
confidence: 99%